2012
DOI: 10.1038/ncb2480
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane stress induces relocalization of Slm proteins and activation of TORC2 to promote sphingolipid synthesis

Abstract: The plasma membrane delimits the cell, and its integrity is essential for cell survival. Lipids and proteins form domains of distinct composition within the plasma membrane. How changes in plasma membrane composition are perceived, and how the abundance of lipids in the plasma membrane is regulated to balance changing needs remains largely unknown. Here, we show that the Slm1/2 paralogues and the target of rapamycin kinase complex 2 (TORC2) play a central role in this regulation. Membrane stress, induced by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
451
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(509 citation statements)
references
References 32 publications
24
451
3
8
Order By: Relevance
“…Enrichment of PS on the cytoplasmic face of caveolae has been reported (Fairn 2013), lend themselves to a hypothesis whereby an individual caveola may function as an organizational unit that can flatten into the PM and release specific lipids that modulate the local lipid environment to respond to changes in cellular stress. Cross talk between mechanosensitive caveolae and cellular lipids strengthens the proposed functional similarity to eisosomes in yeast in which eisosome mechanosensation is translated into alterations in glycosphingolipid metabolism as a protective mechanism (Berchtold et al, 2012;Parton and del Pozo, 2013). We suggest that the loss of CAV1/caveolae from the PM has widereaching and dramatic effects on PM dynamics due to these lipid changes.…”
Section: Discussionmentioning
confidence: 92%
“…Enrichment of PS on the cytoplasmic face of caveolae has been reported (Fairn 2013), lend themselves to a hypothesis whereby an individual caveola may function as an organizational unit that can flatten into the PM and release specific lipids that modulate the local lipid environment to respond to changes in cellular stress. Cross talk between mechanosensitive caveolae and cellular lipids strengthens the proposed functional similarity to eisosomes in yeast in which eisosome mechanosensation is translated into alterations in glycosphingolipid metabolism as a protective mechanism (Berchtold et al, 2012;Parton and del Pozo, 2013). We suggest that the loss of CAV1/caveolae from the PM has widereaching and dramatic effects on PM dynamics due to these lipid changes.…”
Section: Discussionmentioning
confidence: 92%
“…Here a prominent role for Slm proteins is suggested by reports that the PH-domain-containing proteins Slm1 and Slm2 are necessary and sufficient for recruitment of Ypk1 to Torc2 and for Ypk1 activation (Fig. 4D) (Berchtold et al 2012;Niles et al 2012). Furthermore, inhibition of sphingolipid synthesis causes a rapid relocalization of Slm proteins from eisosomes to membrane domains containing Torc2, and this relocalization is required for phosphorylation of Ypk1 at Thr662 (Berchtold et al 2012).…”
Section: Sphingolipid Homeostasis In the Er And Beyondmentioning
confidence: 99%
“…In yeast, the Torc2 kinase complex is a positive regulator of ceramide synthase activity and therefore controls steady-state levels of LCBs and ceramides (Aronova et al 2008). Torc2 activity is in turn induced by sphingolipid depletion (Berchtold et al 2012), suggesting a potential feedback mechanism controlling ceramide production. It is not yet known how Torc2 regulates ceramide synthase.…”
Section: Sphingolipid Homeostasis In the Er And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were brought together by Strádalová et al (5), who showed that the membrane compartment occupied by Can1p (MCC) localized to the invaginations seen with freeze fracture EM, and by Karotki et al (6), who showed that Pil1p localizes to the cytoplasmic surfaces of these invaginations. Additional proteins also associate with these punctate domains, in some cases in a transient fashion (17), and the MCC component is reportedly enriched in ergosterol (18) and influenced by phosphoinositide (6,19,20) and sphingolipid (14,17,(21)(22)(23)(24) levels. Hence, the current yeast model (25,26) proposes that Pil1p and Lsp1p, which contain membrane curvatureinducing BAR domains (6,27,28), together with Seg1p (29,30), form a submembrane complex (6) reportedly influenced by Pil1p phosphorylation (25); this complex then either creates or associates with the MCC domains, presumably inducing an inward curvature.…”
mentioning
confidence: 99%